NEUROSCIENCE LEARNING IN EARLY CHILDHOOD EDUCATION - Naily; Siti Rohimatus Zainiyah; Musdalifatul Mukarromah; Nurul Qomariah; Yayuk Masruroh; Marwati (English Language Teaching Journal, 2024)
Neuroscience is a science that studies the nervous system of the human brain. The main focus of neuroscience involves understanding how brain cells communicate. Research in neuroscience has broad implications, from understanding nerves to applications in education. Neuroscience in early childhood education is a field of research that explores the link between children's brain development and the learning process. In the Al-Qur'an there are many explanations about the brain's function for thinking with the word aql. The urgency of character education in early childhood in neuroscience can be seen from the relationship between environmental stimulation and children's brain development. By providing integrated character education, we can create an environment that supports brain and character development in early childhood. Keywords: neuroscience learning, early childhood education